A novel evolution model of pitting failure and effect on time -varying meshing stiffness of spur gears. (February 2021) - Meng, Zong; Wang, Fulin; Shi, Guixia
Highlights: A novel model of tooth pitting and evolution of a single pit are proposed. The meshing stiffness equation of a single pit and multiple pits is derived. The effect pitting and evolution model on TVMS is studied by the case. TVMS obtained from potential energy method is compared with FEM. Abstract: Time-varying meshing stiffness (TVMS) of gears will decrease when gear fault occurs. Therefore, it can be used as an indication to reflect whether the gear is healthy. A pitting model where the pitting shape is considered as approximately a part of sphere is proposed herein. Then, the evolution model of a single pit is proposed. Formulas for computing the meshing stiffness of external spur gears with the proposed pitting model are deduced. Furthermore, pitting distribution models with four different pitting degrees are established, from perfect to severe pitting. The effect of different pitting degrees on TVMS are detailedly investigate experimentally. Compared with the finite element model, the proposed pitting model and computation method of TVMS is effective.